High speed drives review: machines, converters and applications - Abebe, Robert; Di Nardo, Mauro; Gerada, David; Lo Calzo, Giovanni; Papini, Luca; Gerada, C. (2016)
The development of new power electronic device and high performance magnetic materials are the main technological factors that have led both industries and research community to focus their attention on high speed electrical drives. Several papers have already outlined the electrical machine and/or converter topology choice for certain high speed application. This choice depends on the applications under study. This paper aims to identify the most important high speed applications. For each of them, the main design challenges are highlighted and an overview of available market product is presented.